Interpersonal and communication skills development in nursing preceptorship education and training programmes: a scoping review protocol - Hardie, Philip (HRB Open Res, 2021)
The preceptorship model is an education-focused model for teaching and learning within a clinical environment in nursing. It formulates a professional educational relationship between a staff nurse (preceptor) and student nurse and is based on the provision of providing patient care. Preceptorship is widely acknowledged in the literature as a positive pedagogical approach in clinical nursing education in terms of knowledge and skill acquisition, confidence, and professional socialisation of undergraduate nursing students. However, the literature also widely reports negative interpersonal experiences within this professional educational relationship resulting in negative educational experiences and in some cases, negative patient experiences. Therefore, the authors set out to examine what teaching strategies are being implemented by nurse educators to encourage the development of interpersonal and communication skills in facilitating positive interpersonal relationships between the preceptor, nursing student and patient. This paper outlines the protocol for an exploratory scoping review that aims to systematically and comprehensively map out the available published and unpublished literature on the teaching strategies to develop interpersonal and communication skills in preceptorship education and training programmes. To conduct a systematic and comprehensive scoping review, the review will be guided by the Joanna Briggs Institute and Arksey & O’ Malley (2005) six-stage iterative framework, as well as PRISMA-ScR framework guidelines, to ensure the quality of the methodological and reporting approaches to the review. It is anticipated that the results of the scoping review will inform nurse educators on the current educational practices for developing interpersonal and communication skills in preceptorship education and training programmes and identify any educational practices that are worthy of further consideration for future research.